Reliability and Validity of UMP-KI Items - Fatmawati, Latada (Universiti Malaysia Pahang, 2016)
The article describes the validation process of the UMP Soft Skill assessment items also known as UMWKS. The first section of this article discusses the methods involved in the development of the instrument which includes sampling and procedure for data analysis. The second section explains the development procedure of the (UMP-KI), reliability as well as validity of measurement. The third section describes the data analyses. Finally, the fifth section reports the results, which is the psychometric properties of the measurement.